The Relationship between Environmental Sanitation and the Presence of the Dengue Fever Vector Dengue Fever (DBD) in the Working Area of the Subdistrict Community Health Center Medan Polonia - Saskia Diah Nisa (Journal Health of Indonesian, 2023)
One of the environmental-based diseases is Dengue Hemorrhagic Fever (DHF), which is currently a public health problem. Dengue Hemorrhagic Fever is an infectious disease which is currently a public health problem which often becomes an Extraordinary Event (KLB). To find out the relationship between environmental sanitation and the presence of Dengue Hemorrhagic Fever (DHF) vectors in the work area of the Medan Polonia District Health Center. This research is quantitative research using the Descriptive Correlation method. Using a cross sectional study approach. The sample size in this study was 146 people from a population of 230 people. The sample in this study was obtained using a simple random sampling technique. data collection method using a questionnaire. Univariate analysis uses descriptive statistical tests to obtain an overview. The results of this study show that the proportion of clean water supply incidents with the presence of vector (DBD) is (63.7%). Condition of hangers or piles of cloth with the presence of vector (DBD) (58.9%). Condition of water reservoirs with the presence of vector (DBD) (63.7%). Condition of trash cans with the presence of vector (DBD) (63.7%). The condition of the presence of pots/containers with the presence of Dengue Hemorrhagic Fever (DHF) vectors (63.7%). The related statistical test result is that the condition of the hanger or pile of cloth with the presence of vector (DBD) has a value of (p = 0.004). Water reservoirs with the presence of vector (DBD) have a value of (p = 0.009). The condition of the trash can with the presence of vector (DBD) has a value of (p = 0.015). The presence of pots/containers with the presence of vector (DBD) has a value of (p = 0.005). Through the results of the analysis, it can be concluded that there is a significant relationship between the condition of hangers or piles of cloth, water reservoirs, the condition of rubbish bins and the presence of pots/containers with the presence of vectors (DBD) in the Medan Polonia health center working area. It is recommended that the community health center, village midwife and community collaborate to improve environmental hygiene and health.